Productive Performance, Intestinal Morphology and Carcass Yield of Broilers Fed Conventional and Alternative Diets Containing Commercial Enzymatic Complex - Neto , Roberto Montanhini; Ceccantini, Marcio Ladeira; Fernandes, Jovanir Ines (International Journal of Poultry Science, 2012)
The present study aimed at evaluating the effect of adding a commercial enzymatic complex to conventional and alternative diets on the productive performance, intestinal morphology and carcass yield of broilers. 900 male broiler chicks were used, distributed according to a completely randomized design, with six treatments, with six repetitions each. Two control diets were formulated, one with conventional feedstuffs (T1) based on corn and soybean meal and another alternative (T4), containing corn, millet, meals of soybean, canola and sunflower. From these, other four diets were prepared with reduced nutritional levels of metabolizable energy, digestible amino acids, calcium and available phosphorus, without (T2 and T5) and with (T3 and T6) addition of the enzymatic complex. Enzyme supplementation and conventional ingredients propitiated better feed conversion. The broilers that received the alternative diet and reduced nutritional levels with added enzyme (T6) achieved productive performance, intestinal morphology and carcass yield similar to those fed conventional diets at regular nutritional levels (T1). The addition of enzymatic complex promoted better proliferative capacity of the crypts and villi height. The use alternative feedstuffs and nutritional levels reduction causes production performance loses and intestinal mucosa damages, but the inclusion of enzymes complex proportioned similar results to these feed conditions than conventional diets with regular nutritional density.